The status of lean implementation within South African aircraft maintenance organisations - Murphy, Sean (My University, 2011)
Globally the implementation of Lean techniques has proven to be successful in improving quality while reducing turn around times and costs within aircraft maintenance facilities, including those companies that are of a competitive threat to South African companies. The purpose of this study is to determine the level of Lean implementation within South African aircraft maintenance facilities, due to the lack of current data or research regarding this subject. Quantitative and qualitative data was derived from interviews conducted with senior management of a sample of Gauteng based facilities and the results where triangulated and interpreted to determine both their understanding and the status of Lean within their facilities. Lean implementation was not evident in the maintenance facilities surveyed. The majority of persons interviewed showed a lack of understanding of Lean. There was no evidence of any discernable methodology, such as Six Sigma or the Theory of Constraints, being in place. The results of the study will benchmark South African aircraft maintenance organisations against their global competition and will determine what actions should be undertaken, if any, with respect to Lean, so as to ensure they retain or improve their share of the expanding global and African aviation maintenance market.